Transition from thermally assisted to mechanically driven boundary migration and related apparent activation energies. (September 2018) - Renk, O.; Pippan, R.
Abstract: Grain boundary migration during deformation of nanostructured materials has been reported for a variety of materials and loading conditions. As boundary migration occurs even under cryogenic conditions, it is believed to be mainly mechanically driven, although results suggest thermal assistance. Yet, these contributions could not be separated and the underlying apparent activation energies remain uncertain. Here we present an approach that is capable to determine the average activation energies for mechanically driven boundary migration. While the apparent activation energy is increasing with temperature, below critical temperatures it becomes zero, indicating the existence of an entirely mechanically driven regime. Graphical abstract: Unlabelled Image